LIMBAH PEMANENAN JATI DI BAYUWANGI JAWA TIMUR - Juang Rata Matangaran; Romadoni Anggoro (Forestry Faculty of Universitas Hasanuddin, 2012)
Harvesting teak in Java always causes wood waste in the forest. The objectives of this research were to identify the shape of wood waste generated from teak harvesting activities and to determine their recovery and residual factors. The research was conducted at teak forest of Stated Owned Company (Perum Perhutani) at Banyuwangi East Java with the sampling intensity of 10 % using whole tree method. Measurement of wood waste was performed at thinning and clearcutting compartment of teak stand. The result of the study showed that the shapes of wood waste consisted of broken stem, decay wood, short trimming, branch and twig , stump, and irregular wood shape. The recovery and residual factors of the teak harvesting utilization were 79.61 % and 20.39%, respectively. Most of the wood waste were utilized by the local community for energy sources. Key words: Recovery factor, residual factor, teak, wood waste